2019
DOI: 10.1007/s00432-019-02840-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cancer–testis antigens in esophageal cancer and their progress in immunotherapy

Abstract: Purpose Esophageal cancer is a common disease in China with low survival rate due to no obvious early symptoms and lack of effective screening strategies. Traditional treatments usually do not produce desirable results in patients with advanced esophageal cancer, so immunotherapy which relies on tumor-related antigens is needed to combat low survival rates effectively. Cancer-testis antigens (CTA), a large family of tumor-related antigens, have a strong in vivo immunogenicity and tumor-restricted expressing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 92 publications
2
40
0
Order By: Relevance
“…Among these tumour samples, 20-30% exhibited MAGE-A4, NY-ESO-1 and/or SAGE expression. The MAGE-A, NY-ESO-1 and SAGE expression rates in this study were comparable to those reported previously [11,12,[21][22][23][24][25][26][27]. Among the 585 tumour samples, 214 oesophageal cancer samples were evaluable for the expression of all 3 CT antigens.…”
Section: Discussionsupporting
confidence: 89%
“…Among these tumour samples, 20-30% exhibited MAGE-A4, NY-ESO-1 and/or SAGE expression. The MAGE-A, NY-ESO-1 and SAGE expression rates in this study were comparable to those reported previously [11,12,[21][22][23][24][25][26][27]. Among the 585 tumour samples, 214 oesophageal cancer samples were evaluable for the expression of all 3 CT antigens.…”
Section: Discussionsupporting
confidence: 89%
“…comparable to those reported previously [11,12,[21][22][23][24][25][26][27]. Among the 585 tumour samples, 214 oesophageal cancer samples were evaluable for the expression of all 3 CT antigens.…”
Section: Eso-1 And/or Sage Expression the Mage-a Ny-eso-1 And Sagesupporting
confidence: 84%
“…Currently, overexpression of TTK was confirmed to occur in various cancers that harbor copy number gains (CNG) of chromosome 9p involving PD-L1. [ 33 ] Furthermore, TTK was overexpressed within the incredible lions share of esophageal squamous cell carcinoma tissues but barely expressed in ordinary tissues, [ 34 ] while another study demonstrated that high expression status of TTK corresponded positively with tumor grade and negatively with prognosis in glioblastoma. [ 35 ] Nowadays, there are few types of researches regarding the role of TTK in PCa.…”
Section: Discussionmentioning
confidence: 99%